(untitled) (Milton Keynes, England, 1989)
This second edition retains the general structure of the first edition, but has been updated in the light of recent oceanographic research, and improved as a teaching text on the basis of feedback from past students and other readers.
Keywords: Ocean circulation,Sự lưu thông của đại dương